Employee Engagement Ditinjau dari Pengembangan Karier dan Kesejahteraan pada Karyawan - Trefilona, Clirista Grasialika; Astuti, Rr Dwi (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
Employees are every individual who can produce goods and facilities through work in order to meet their own needs and the needs of the community, either inside or outside the employment relationship. The purpose of this study is more interested in knowing empirically related to employee engagement in terms of career development and welfare in employees at PT X. The research method used in this research is quantitative research method. The results of this study obtained data by link google form using two items, namely favorable and unfavorable on the 24-item employee engagement scale, 45-item career development and 39-item welfare distributed to 133 employees of PT X with the provisions of men and women in the age range of 18-43 years, the average education of SMK to S1 with a tenure of more than 1 year - 3 years and above. This indicates that there is a positive relationship of 0.000 (p<0.01) between career development and employee well-being with employee engagement in employees and there is a positive relationship between employee engagement, thus the hypothesis proposed in this stuy is accepted.